Residents perception of and participation in solid waste recycling in Langkawi / Muhammad Azizan - Azizan, Muhammad; Zulkeflli, Adie Effendi; Azizan, Kamil (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Success of waste separation at source depends on the willingness of, and good practices among residents. Nowadays, managing household solid waste is a growing challenge for many cities, which is important for environmental conservation. In order to tackle this problem, local authority is turning towards recycling, which is an effective tool for solid waste management. Participation rate of waste separation among Malaysians is still low; thus, there is an urgency to foster waste separation practice beginning from the household. This research seeks to understand the residents’ perception of, and participation in recycling activities in Langkawi to achieve environmental conservation in the context of island tourism. Recycling in Malaysia is protected by the law, under Solid Waste and Public Cleansing Management Act, 2007 (Act 672). The Separation at Source Initiative (SSI) became effective on September 2015 with mandatory requirement for residents to separate waste in their dwelling. A multiple acceptance dimension (socio-political, community, market, and technology) were discussed thoroughly in the context of island tourism (Langkawi) to explain resistance from the household towards SSI. The study involves a quantitative survey to understand the residents’ perception and participation landscape, and also factors affecting recycling behaviors and attitudes of residents in Langkawi. In measuring residents’ perception towards the recycling program, quantitative results from survey responses were used to create civic engagement, a recycling satisfaction, and a behavior score. As an outcome, the study strongly suggests that Langkawi local authority further develop an aggressive educational policy through program and activities, incentive policies, and craft a Master Plan to encourage a more robust public participation in continuous improvement of environmental conservation that would endure generations.